Strategic management and innovative applications of e-government - Molnar, Andreea 1984 (Advances in electronic government, digital divide, and regional development (AEGDDRD) book series, 2019)
"This book examines current issues relating to the practice of electronic government. It provides organizational and managerial directions with greater use and management of electronic/digital government technologies in organizations. It also covers topics such as e-government adoption and diffusion, e-government policy, e-government planning and management, e-government applications, and e-government impacts"